Principles of digital design - Gajski, Daniel D. (Prentice Hall, 1997)
This book is designed to facilitate a thorough understanding of fundamental principles without requiring readers to memorize an excess of confusing technological details. Rather than focusing on techniques for one particular phase of design, it covers the complete design process, from specification to manufacturing.